34P Development of LAG-3 nanobodies as potent cancer imaging tracers. (15th December 2019) - Lecocq, Q; Awad, R M; Zeven, K; Vlaeminck, Y De; de Mey, W; Debie, P; Puttemans, J; Goyvaerts, C; Raes, G; Keyaerts, M; Devoogdt, N; Breckpot, K
Abstract: Background: Immune checkpoint blockade revolutionized anti-cancer therapy but unfortunately not all patients can benefit from it. The development of innovative and efficacious diagnostic methods that can guide treatment decisions is warranted. Nanobodies (Nbs) are small antigen-binding moieties that efficiently penetrate cell-cell interfaces in tumors and generate high contrast in noninvasive imaging, making them prime candidates for development of novel imaging tracers. In this study, we generated and characterized Nbs as tools for nuclear imaging of the immune checkpoint LAG-3. Methods: Nanobody generation was initiated by immunization of llamas with recombinant LAG-3. Periplasmic extracts were generated and analyzed for their binding to mouse LAG-3 using ELISA and flow cytometry. Selected Nbs were cloned in a vector for high yield production and purified in order to analyze their affinity using SPR. A total of 9 high affinity Nbs were subsequently evaluated for their labeling efficiency with Technetium-99m ( 99m Tc), after which the biodistribution of 99m Tc labeled Nbs was assessed in mice. Additionally, we evaluated the noninvasive detection of LAG-3 expressed by immune cells in the tumor environment of murine colon adenocarcinoma (MC38) using 99m Tc-Nb3132. Results: Nine high affinity Nbs were selected to evaluate their potential as noninvasive imaging tracers. Subsequently, Nb3132 was reported as the most potent tracer for noninvasive imaging of the immune checkpoint LAG-3 (1) . SPECT/CT of MC38 tumor-bearing mice 1h after injection of 99m Tc-Nb3132 presented specific uptake in spleen, thymus, lymph nodes as well as at the tumor site. This uptake pattern coincided with the presence of LAG-3 expressed on immune cells in these organs, as determined by flow cytometry and immunohistochemistry. No specific uptake was observed when injecting mice with a radiolabeled control Nb. Conclusion: Nb3132 showed excellent in vivo imaging capacities to specifically identify LAG-3 expressing immune cells within the tumor site. These findings support the predictive potential of Nb3132 to noninvasively detect LAG-3 by nuclear imaging and to guide treatment decisions in future, improving the shortcomings of using full-sized antibody formats as diagnostic tracers. Legal entity responsible for the study: Geert Raes. Funding: Kom op tegen kanker and FWO flanders. Disclosure: All authors have declared no conflicts of interest.